Analisis Interaksi antara Pembelajaran RME Berbantuan Adobe Flash CS6 dengan Kemampuan Awal Matematika dalam Meningkatkan Literasi Matematis - Umbara, Uba; Nuraeni, Zuli (Jurnal Elemen, 2019)
This study aims to analyze the interaction between the RME approach and conventional with the initial ability of mathematics in improving students' mathematical literacy. The research method used in this study was quasi-experimental with the design of a non-equivalent control group design. Data retrieval is done through mathematical literacy tests. The data analysis method that the researchers conducted was the Two-Way Analysis of Variance (ANOVA) using the general linear univariate analysis model. The subjects in the study were grade VIII students of SMP Negeri 3 Kuningan, which numbered 309 students. The sampling technique was carried out using purposive sampling technique, taking into account the homogeneity of Prior Mathematical Learning Abilitystudents'in both classes determined by giving initial tests to students. The research sample amounted to 65 students, which were divided into two classes. The results of the study showed that there was no interaction between RME learning and the conventional category of students 'ability to students' mathematical literacy. However, for each level of students’ initial mathematical abilities, an increase in students' mathematical literacy skills with learning using the RME learning assisted by Adobe Flash CS6 is higher than students who obtain conventional learning.